THE EFFECTIVENESS OF STUDENT INTERVENTION PROGRAM - MY ADVISEE PROGRAM OUTCOMES (PO) - Syed Muhammad Bin Syed Yahya; Nurul Farraheeda Binti Abdul Rahman; Nurul Ain Umaiban Binti Yusof; Azyan Zafyrah Binti Mohd Zahid (Journal of Islamic, Social, Economics and Development, 2021)
The Faculty concerns about the performance of the program outcomes (PO) of Diploma Student in Civil Engineering. Therefore, ‘My Advisee POs’ is carried out every semester to the students that have less than 50% of their PO attainment in the previous semester which is after completing the fundamental and intermediate courses of the examination result. Involvement of the Lecturer in Charged (LIC), Team Teaching, and Academic Advisor (AA) is monitored closely by the Head of Studies and Outcome-Based Education (OBE) Committee to ensure the program is successful and improvement of the PO is visible. The LIC and Team Teaching are responsible for selecting and conducting one or half-day programs such as seminar/ webinar/ technical talk/ simulation/ competition subjected to their PO. In sessions with the AA, students will receive guidance and support through the offer of appropriate advice including referral to appropriate support systems, e.g., learning support program, online resources, counselling, referral to relevant academic or administrative points of contact, such as Buddy System Coordinator, Academic and Student Affair and extra tutorial support from the Faculty’s intervention program. This paper describes a survey tool, called the Program Effectiveness Survey, which can be used to evaluate and improve the effectiveness of the program. The tool provides feedback from students on the outcomes and understanding of the virtual webinar programs and how it could be improved. The survey was found to have a relatively high percentage, but reliability was below appropriate levels.